Peanut response to different sources and doses of phosphorus (Research, Society and Development, 2021)
In Brazil, peanut production grows annually. In the state of Minas Gerais, to achieve crop productivity, nutritional investment is essential and one of the main nutrients for peanut development is phosphorus. Due to the scarcity of information on peanut production in the Cerrado Mineiro, the experiment aimed to evaluate the influence of phosphorus doses and sources in the peanut tree. The statistical design used was randomized blocks (DBC), distributed in two factorial schemes, one being 5 x 2 x 6 (doses x sources x evaluon seasons) during crop development and the other 5 x 2 (doses x sources) at the end of the cycle, at the time of production. The treatments consisted of 5 phosphorus doses (0, 40, 80, 120, 160 Kg ha-1), 2 phosphorus sources (single superphosphate and triple superphosphate) and 6 evaluation seasons (15, 30, 45, 60, 75 and 95) days after emergence. In the 2 designs there were 4 repetitions. Growth and yield analyzes were performed. With the analysis it was possible to observe that superphosphate source ensured greater contribution of leaf area and dry matter, but at plant height the best source was triple superphosphate with doses 40 and 160 kg ha-1. Due to the contribution of dry matter, structural improvement of the culture and a 21.51% lower cost, it was concluded that the best source of phosphorus to be used is simple superphosphate.